Skid Resistance of Asphalt Concrete based on Mixture and Aggregate Characteristics: Predictive Model Development for Thailand - Chotisakul, S.; Siripun, S.; Jitsangiam, Peerapong; Horpibulsuk, S.; Sangpetngam, B.; Subsompon, W.; Wongweeranimit, W.; Chanhom, P. (Suranaree University of Technology, 2014)
This research aims to produce a new predictive model of skid resistance in asphalt concrete, with a particular focus on Thailand. Skid resistance in road pavements is an inherent safety factor affecting vehicle users. Thus improvements in this area will greatly enhance road network safety in Thailand. A skid resistance predictive model, based upon the essential aggregate and mixture characteristics that significantly relate to the skid resistance values of asphalt concrete was developed. In this study, three types of aggregate (limestone, granite and basalt) were collected. These aggregates, obtained from 14 provinces in Thailand were representative of all of Thailand’s aggregates. Petrographic Analysis, Gradation tests, Aggregate Impact tests (AIV), Aggregate Crushing tests (ACV), the Los Angeles Abrasion (LA) test, Soundness tests, Polishing Stone tests (PSV) and the British Pendulum Test (BPT), along with the standard mix design were performed. These procedures determined all the essential characteristics in the mixtures and aggregates of asphalt concrete. The results of the research demonstrate that some aggregate characteristics are statistically significant in their relationship to the skid resistance values of asphalt concrete mixtures. These findings will be embraced in the preventive scheme under the strategic road safety management of the Department of Rural Roads, Thailand.